Conductive ITO Interfaces for Optoelectronic Applications Based on Highly Ordered Inverse Opal Thin Films. Issue 4 (6th February 2020) - Galle, Lydia; Ehrling, Sebastian; Lochmann, Stefanie; Kaskel, Stefan; Bischoff, Lothar; Grothe, Julia
Abstract: A three‐step fabrication process for optically transparent, conducting ITO thin films with an intrinsic inverse opal structure is described. The preparation is based on colloidal crystal templating using polystyrene microspheres (100 nm–600 nm). For the realization of varying periodicities in this structure, different sphere sizes were assembled to monolayers on a substrate by spin coating and infiltrated afterwards similarly. The influence of rotation parameters as well as dispersion concentration was studied. Using this approach different geometries of the surface are accessible by systematically varying the rotation parameters and infiltration volume. The thin films show excellent anti‐reflection behavior, good transmission (>80% in the visible range) as well as a low resistance of 200 Ω/sq compared to other porous ITO interfaces. The properties are very promising for several optoelectronic applications such as in‐ or out‐coupling structures in solar cells and organic light emitting diodes. Abstract : Order, order : A three‐step fabrication process for optically transparent, conducting ITO thin films with an intrinsic inverse opal structure is described.